Evaluation of the benefit with the use of the sound amplification inchildren and teenagers - Aurélio, Nilvia Herondina Soares; Torres, Enma Mariángel Ortiz; Lopes, Aline da Silva; Costa, Maristela Julio (Arquivos Internacionais de Otorrinolaringologia, 2012)
Objective: Evaluate the proportionate benefit by the sound amplification in children and teenagers attended by the program of hearing health attention by the Federal University of Santa Maria (UFSM).Method: Participated from these study 63 individuals with age between 3 and 14 years and their family. For the evaluate the benefit proportionate by the sound amplification was applied the Infant Toddler Meaningful Auditory Integration Scale (IT-MAIS), for children with less than 4 years old; the Meaningful Auditory Integration Scale (MAIS), for infants from 4 to 7 years and the questionnaire of evaluation from the benefit in infants and young, for the individuals from 8 to 14 years.Results: Only one individual could be evaluated through the MAIS scale, and the average punctuation found in the evaluation of the hearing behaviors was of 19,9. Were evaluated 52 individuals through the questionnaire of evaluation of benefit in infants and teenagers, and the positive answers related to the benefit proportionate by the prosthesis in different situations were the most found in all items.Conclusions: Was verified the benefit proportionate by the sound amplification, in different situations of daily life, such as from the patient's perspective as from his family. In some cases, where were found little or none benefit, there were influence of others clinical alterations, besides the hearing loss, influencing the effective use of the hearing aids.
Keywords: hearing; hearing loss; auxiliary from hearing; children; questionnaire